Compartment syndrome: a rare complication following laparoscopic colorectal surgery. Issue 3 (2nd March 2021) - Crane, Jasmine; Seebah, Kevin; Morrow, Darren; Pal, Atanu
Abstract : We present a 71-year-old man who developed left calf pain after an elective laparoscopic assisted anterior resection. A clinical picture with a raised creatine kinase and negative Doppler ultrasound was suggestive of compartment syndrome. Successful surgical management was performed with two incisional fasciotomies to release all four compartments of the left leg. The patient recovered well postoperatively. The lateral incision was closed primarily while the medial incision required vacuum-assisted closure dressings and healed by secondary intention. Neither wound required skin grafts. The patient recovered well but had an extended hospital stay due to extensive physiotherapy requirements and mild foot drop. This report is intended as a guide for clinicians when considering differentials in calf pain following surgery and to keep in mind the small risk of developing compartment syndrome after pelvic surgery.